Creative actions : embedding creative competencies in every classroom - Patston, Tim; Kaufman, James C.; Cropley, David (Moorabbin, Victoria : Hawker Brownlow Education, 2022)
We believe that schools can significantly improve the creative competencies of both teachers and students by leveraging assets they already have, learning a few new things and striving for sensible and sustainable incremental change. In other words - slow food creativity rather than fast food creativity.We also believe that teachers can learn a lot from each other, both within their own subjects but more importantly from teachers who teach other subjects. We have included examples from teachers and subjects around the world to show you that teachers have the capacity and curiosity to succeed. Our experience in schools shows us that teachers are willing and able to face the challenges and opportunities in building their competencies as creative educators, despite some of the barriers they are facing.
Includes bibliographical references (pages 232-268) and index.
Keywords: Creative teaching; Creative thinking; Creative ability; Education; Australian